Design and Simulation of Single Electron Transistor based SRAM and its Memory Controller at Room Temperature - Parekh, Rutu (International Journal of Integrated Engineering, 2019)
Heterogeneous 3D integration of single electron transistor (SET) circuits with CMOS based circuits is achieved by stacking a SET layer above CMOS IC. Low power and delay efficient circuits can be designed using SET. In this paper, we have designed and simulated 6T SRAM array operating at room temperature and at CMOS comparable voltage. Peripheral circuit like sense amplifier, decoder, write circuit and pre-charge circuit using SET have been designed for optimum performance. The stability of 6T SRAM cell is verified using N-curve method. The designed SET based 8 x 8 bit SRAM is 99.54 % power efficient, 92.19 % faster in write access time and 78.58 % faster in read access time compared to 16 nm CMOS based SRAM. The SRAM is designed to work at CMOS comparable voltage of 800 mV, which can be scaled up to 20 mV with better efficiency. The designed SRAM is tested and verified for variation in process, voltage and temperature. The maximum frequency of operation for the designed SET based SRAM with memory controller is 4 GHz.